Nanocomposite starch films: Cytotoxicity studies and their application as cheese packaging - Ortega, Florencia (2023)
This work focuses on the development of starch-based nanocomposite films containing AgNPs obtained by different green synthesis techniques, the characterization of their relevant properties, the study of their cytotoxicity and their application as food packaging on cheese. AgNPs were obtained by different green synthesis techniques: AgNP in situ and AgNP L. The incorporation of AgNP L improved the barrier properties of nanocomposite films, since water vapor permeability decreased (0.63 ± 0.07 × 10-10 g/m s Pa) compared to films containing AgNPs in situ (1.9 ± 0.1 × 10-10 g/m s Pa), while the UV–vis barrier capacity was higher (371.5 ± 15.6 and 314.1 ± 14.7, respectively). Films with AgNPs synthesized in situ were less cytotoxic for the Caco-2/TC7 line (90% viability) in comparison with films containing AgNPs synthesized with lemon juice (AgNP L). Vero cells were susceptible to adhesion problems on both control and nanocomposite films. Likewise, the differences observed between monocytes and macrophage THP-1 cells may be associated with the expression of different markers. Then, active packages were developed by thermo-sealing the films. The nanocomposite samples were able to extend the shelf life of cheese by 7 days, but the CL and AgNP L films were more effective, probably due to the synergistic effect of the active compounds present in the lemon juice and the low pH of the film-forming suspension. Finally, production costs and the current legislative framework for this type of material were revised.